Variation and change in the history of the stressed mid vowels of the Portuguese language: an interpretation of the rhymes of the poetry from the past - Fonte, Juliana Simões (2023)
This research aims to investigate the pronunciation of the stressed mid vowels in Portuguese of the 13h, 15h, 16h and 17h centuries, through the observation of the rhymes of the poetry from that period. The corpora comprise the Cantigas de Santa Maria by Alfonso X, the Cancioneiro Geral by Garcia de Resende, Os Lusíadas by Camões and the sonnets by Gregório de Matos. Knowing that the ancient writing, like the present, had only two graphemes to represent phonemes concerning stressed mid vowels of Portuguese, the possibilities and impossibilities of rhyme between mid vowels represented by identical graphemes were evaluated in this work. The results of this research suggest that there was constant phonetic variation in the speech of the stressed mid vowels of the Portuguese language, between the 15th and 17th centuries (at least), and that, in some cases, this variation resulted in a change, throughout the history of the language.